What happens in Vegos does not stay in Vegos - Barczi, Šimon; Lahvička, Jiří, 1975-; Svoboda, Miroslav; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
The main objective of this paper is to measure and examine demand for commodities offered in the Los Vegos bar in Marianske Lazne. In my experiment, I will be randomly changing price of draught beer in range from 23 to 33 CZK for 30 consecutive days. Each day, I will observe consumption of all goods offered in the bar. I will also analyze a year-long time line with detailed consumption of every product the bar offers . I will measure the own-price elasticity of beer and the cross-price elasticities of other products. My paper will be useful for bar owners to set an optimal price and stock of the goods they offer.
Vedoucí práce: Jiří Lahvička
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses